Interpreting trauma radiographs - McConnell, Jonathan (John Wiley & Sons, 2008)
As advanced practices and role extension within the healthcare sector continues unabated, increasingly practitioners seek ways to widen their professional remit and develop and add to their skills. Interpreting Trauma Radiographs provides a unique guide to enable radiographers and trained healthcare professionals to confidently and competently interpret and report on radiographic images. Designed specifically for radiographers, casualty (accident and emergency) medical officers and trainees, and other health professionals who regularly encounter trauma radiography as part of their work, this b.